(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the accuracy of High Resolution Computed Tomography in the evaluation of Diffuse interstitial lung disease. Study Design: Descriptive study. Place and Duration of Study: This study was conducted in the Department of Diagnostic Radiology, Pakistan Institute of Medical Sciences, Islamabad during the year June 2008 to December 2008. Materials and Methods: 30 patients were selected from OPD and Emergency department with history, clinical signs and plain chest radiograph suggestive of diffuse lung disease. Multi-slice high resolution spiral CT scanner “Asteion VR” (Toshiba) was used to conduct the study with High Resolution Computed Tomography (HRCT) protocol used in the evaluation of diffuse lung disease. Results: The 30 patients included in this study comprised of 15 male and 15 females with a male to female ratio of 1:1. The mean age of patients was 50.33 years. Cough was present in 100% of patients, dyspnea (83%), hemoptysis (17%), body aches (43%), joint pains (13%), and occupational exposure (23%). Different clinical signs were wheezing (70%), coarse crepitation’s (47%) and clubbing (7%). In this study of all 30 patients (n=30) sarcoidiosis was (23%), pneumoconiosis (27%), idiopathic pulmonary fibrosis (20%), extrinsic allergic alveolitis (7%), lymphangitic carcinomatosa (10%) and systemic sclerosis (3%). Normal or non-diagnostic chest X-rays were seen in 20% patients which were then diagnosed by HRCT. The inter observer agreement on chest X-rays was found to be around 27% and that of HRCT is 52%. Conclusion: HRCT is the diagnostic tool of choice in the diagnosis of diffuse interstitial lung disease.